Assessing the cyto-genotoxic impacts of un-neutralised and pH-neutralised acid mine drainage on the human breast cancer cell line, MCF-7 - Botha, Shirmone (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.